Desenvolvimento de banhos para eletrodeposição de ligas Zn-Fe-P e Zn-Ni-P - Mattos, Luciana Vieira (2015)
In this work, an alkaline and an acid bath, both containing sorbitol, for electrodeposition of Zn-Fe-P on Pt were developed. Furthermore, we also developed an acid bath, containing sorbitol and H3BO3 for electrodeposition of Zn-Ni-P on Pt. The characterization of plating baths by potentiometric titration showed in which pH the species of metallic ions were soluble and stable. The voltammetric studies indicated the possible co-deposit Zn, Fe and P and Zn, Ni and P from the proposed baths. Accordingly, the voltammetric curves of the individual metals obtained in the absence and presence of hypophosphite, for the three proposed baths, showed that this compound changed voltammetric deposition and dissolution profiles for Zn-P, Fe-P and Ni-P, suggesting the formation of these alloys. EDX analysis was used to confirm the co-deposition of Zn-Fe-P and Zn-Ni- P. Furthermore, indicate a critical potential where the alloy becomes rich in zinc in the Zn-Fe-P deposits system and shows that Zn-Ni-P deposits depends to ED and qD. Furthermore, it was possible to observe an inhibition behavior between Zn and P produced from the alkaline bath deposition of Zn-Fe-P and deposits obtained from the bath deposition of Zn-Ni-P. SEM analysis showed that Zn-Fe-P obtained from the alkaline bath was more superior than Zn-Fe-P deposits obtained from the acid bath and Zn-Ni-P deposits because it is, most often, uniform and doesn t have cracks neither dendrites. XRD analysis indicated that both Zn-Fe-P alloys as Zn-Ni-P alloys are formed by a mixture of phases.